(untitled) (Vietnam Journal of Community Medicine, 2024)
Target: Assessing the readiness to discharge patients undergoing spinal surgery at the spinal surgery department of Viet Duc University Hospital. Methods: A cross-sectional descriptive study was conducted on 120 patients discharged from the spine surgery department of Viet Duc University Hospital from February 2024 to June 2024; Use the Readiness for Discharge Scale (RHDS) to survey information about patients’ readiness for discharge from the hospital. Results: According to statistical results, the male/female ratio is 1,6/1; Average age: 48,9 ± 12,8 years. The total average score of the RHDS is 182,35 ± 12,23, in which: the personal status score is 8,08 ± 0,51; knowledge score is 8,54 ± 0,92; The coping ability score is 8,92 ± 0,78 and the social support score was 9,69 ± 0,66. Conclusion: The readiness for discharge of 120 spine surgery patients was high. Recommendations: Identifying factors that predict readiness or lack of readiness is necessary to determine the appropriate timing of discharge and post-discharge follow-up needs. Therefore, more research needs to be conducted to assess patients’ readiness for discharge, then improving the quality of care and patient satisfaction.